The Influence of Psychological Safety, Reward Fairness, and Mindfulness at Work on the Workplace Well-Being of Employees of Technology Startup Companies - Fatimah Malini Lubis; Atika Dyah Perwita; Tyahya Whisnu Hendratni; Elisa Khairani; La Juli; Nasruddin Khalil Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research is aimed to determine the effects of psychological safety, fairness in rewards, and mindfulness at the workplace on the well-being of employees in a tech startup. Employees' well-being is likely to be supported by the startup's dynamic and high-pressure work environment. The study is quantitative, with an explanatory approach, and has a sample of 180 respondents, who are purposively selected employees of a tech startup company. A questionnaire based on a five-point Likert scale is used for data collection, and multiple linear regression is employed for analysis. The findings reveal that psychological safety, reward fairness, and mindfulness at the workplace not only influence the well-being of employees positively but also significantly. The study's findings on a theoretical level expand the territory of organizational behavior and HR management studies concerning work well-being in the scenario of technology startups. Besides, if the management takes into account the results of this research, they would gain a better understanding of the psychological safety, fairness of reward systems, and mindfulness practices areas within their employees that support work policies for continuous improvement in well-being.